Compositional engineering of solution-processed BiVO4 photoanodes toward highly efficient photoelectrochemical water oxidation. (January 2018) - Byun, Segi; Jung, Gihun; Moon, Song-Yi; Kim, Bumsoo; Park, Jeong Young; Jeon, Seokwoo; Nam, Sung-Wook; Shin, Byungha
Abstract: While BiVO4 is a promising photoanode for solar-driven photoelectrochemical (PEC) water splitting, fine control of its chemical composition (Bi/V ratio) and modification of its electrical properties via extrinsic doping are necessary to improve its PEC performance. Here, we performed compositional engineering of BVO—varying Bi/V ratio and inclusion of different concentrations of Mo dopants. Through physical and chemical analyses, we found that the materials properties of BiVO4 and its PEC performance were highly sensitive to the chemical composition. Our optimized BiVO4 -based photoanode exhibited the highest photocurrent density among the state-of-the-art SnO2 /BiVO4 heterojunction photoanodes reported in the literature: 2.62 and 4.20 mA cm −2 measured at 1.23 V vs. a reversible hydrogen electrode for the oxygen evolution reaction and sulfite oxidation reaction, respectively. A complete picture explaining various PEC performances with different chemical compositions via the band structure of BiVO4 has emerged. This work points to the importance of specific control of the chemical composition in achieving highly efficient BiVO4 -based photoanodes, which will guide future research directions in the fabrication of other high performance photoelectrodes. Graphical abstract: Highlights: Highly efficient SnO2 /BiVO4 photoanodes are achieved by engineering its composition. The material and PEC properties of BiVO4 are affected by its chemical composition. The improved PEC performance is correlated with band alignments of SnO2 /BiVO4 . Our optimized sample exhibits superior performance in PEC water oxidation.